Implementation in Providing Warm Compresses to Reduce Pain in the Elderly with Gout Arthritis at UPT Yansos Tuna Rungu and Wicara Pematangsiantar - Damanik , Dinda Ayu Diah; E.P.P, Riska Wani (COVID-19 : Journal of Health, Medical Records and Pharmacy, 2024)
Gout arthritis is an inflammation of the joints caused by the buildup of crystals in the joints due to impaired purine metabolism in the body. Purines are proteins that undergo metabolism in the body that are converted into uric acid. The purpose of this study is to describe Nursing Care for the elderly with Gout arthritis in the provision of warm water compresses to reduce pain in Upt Yansos for the Deaf and Speech Pematangsiantar. The design of this study is descriptive using a case study method on 2 clients with Gout arthritis who experience acute pain with purposive sampling techniques. Data were collected by interview, observation, and physical examination techniques carried out using the gerontic askep assessment format, warm compress SOP. The results of the assessment found that the client complained of pain with a pain scale of client I and client II, which was 5. After being given warm compresses, the pain scale in client I and client II decreased, namely on the first day with a pain scale of 5, on the second day the pain scale was 4, and on the third day the pain scale became 3. After 3 days of nursing treatment, the act of giving warm water compresses is very effective in reducing acute pain in patients with Gout arthritis. For nurses to teach care to patients with gout arthritis. For patients about maintaining health and a healthy lifestyle.